1998
DOI: 10.1105/tpc.10.2.255
|View full text |Cite
|
Sign up to set email alerts
|

A Plant Homolog of the Neutrophil NADPH Oxidase gp91phox Subunit Gene Encodes a Plasma Membrane Protein with Ca2+ Binding Motifs

Abstract: Rapid generation of O 2 Ϫ and H 2 O 2 , which is reminiscent of the oxidative burst in neutrophils, is a central component of the resistance response of plants to pathogen challenge. Here, we report that the Arabidopsis rbohA ( for respiratory burst oxidase homolog A ) gene encodes a putative 108-kD protein, with a C-terminal region that shows pronounced similarity to the 69-kD apoprotein of the gp91 phox subunit of the neutrophil respiratory burst NADPH oxidase. The RbohA protein has a large hydrophilic N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
220
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(227 citation statements)
references
References 37 publications
6
220
0
1
Order By: Relevance
“…Thus, appearance of Á O 2 À that is possibly produced by NADPH oxidase is linked to accessibility to Bgh (Hu È ckelhoven and Kogel, 1998). ROIs from NADPH oxidase activity are required for cell growth by regulating different processes, including calcium uptake, which might feed back NADPH oxidase activity that is Ca 2 stimulated (Keller et al, 1998;Sagi and Fluhr, 2001). Although participation of the NADPH oxidase in barley±Bgh interaction seems possible, we do not exclude other explanations, e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, appearance of Á O 2 À that is possibly produced by NADPH oxidase is linked to accessibility to Bgh (Hu È ckelhoven and Kogel, 1998). ROIs from NADPH oxidase activity are required for cell growth by regulating different processes, including calcium uptake, which might feed back NADPH oxidase activity that is Ca 2 stimulated (Keller et al, 1998;Sagi and Fluhr, 2001). Although participation of the NADPH oxidase in barley±Bgh interaction seems possible, we do not exclude other explanations, e.g.…”
Section: Discussionmentioning
confidence: 89%
“…The NADPH oxidase gene family is composed of 10 Rboh genes (Torres et al, 1998;Dangl and Jones, 2001) encoding plasma membrane proteins that display a cytosolic extension with two Ca 2+ -binding EF hands, likely responsible for their regulation by Ca 2+ (Keller et al, 1998). NADPH oxidase rapidly reduces apoplastic O 2 to O 2 2 as a primary product that then may be further converted to H 2 O 2 (Neill et al, 2002).…”
Section: Atrbohd Helps Mediate Ros Signaling In Seedlings/shoots Undementioning
confidence: 99%
“…The first report of a plant RBOH revealed that unlike its mammalian homologue gp91 phox , it possesses additional potential regulatory EF-hand domains within an N-terminal extension (20). Like mammalian NADPH oxidases, plant RBOHs are transmembrane proteins that transfer electrons from intracellular NADPH across the plasma membrane before they are coupled to molecular oxygen in the apoplast to produce O 2 -and its subsequent dismutation product, H 2 O 2 ( Fig.…”
Section: Production Of Rois By Nadph Oxidasesmentioning
confidence: 99%